In Vivo Toxicological and Microbiological Activity of Marrubium vulgare L. on Candida albicans Isolated from Nosocomial Infections - Mahmoud Adel Chabane; Aicha Tir Touil; Belkacem Khelladi; Boumediene Meddah; Meriem Mokhtar (Tabriz University of Medical Sciences, 2020)
Background: The objective of this study was to test the toxicology and microbiological of methanolic extract of Marrubium vulgare "MEMV" in rat and its efficiency in the treatment of systemic candidiasis. Methods: Forty (40) male rats (Wistar type) were divided into four groups (10 rats /group) where the toxicological, microbiological and histological studies were applied. Later, the infection with 107 cells /ml of Candida albicans and the curative treatment were applied by the daily administration with a gavage of 800 mg/kg of MEMV. Results: The toxicology studies indicated that the dose of MEMV at 800 mg/kg of body weight was not harmful. The microbiological and histological analysis showed that the treatment with MEMV of rat colonized with 107 cells/ml of Candida albicans limits the multiplication of the yeast in the intestine and colon of the colonized rat. The translocation of Candida albicans in liver, spleen and lungs in rat which was treated with 800 mg/kg of MEMV was significantly lower than in controls to seven post-infection days. However, we did not detect yeast in the kidneys and hearts of the infected treated groups and the infected untreated ones. Conclusion: Our results suggest that MEMV limits the gastrointestinal colonization and dissemination of Candida albicans in the other organs.